Multistep Crystallization Pathways in the Ambient‐Temperature Synthesis of a New Alkali‐Activated Binder. (1st November 2021) - Maslyk, Marcel; Gäb, Tobias; Matveeva, Galina; Opitz, Phil; Mondeshki, Mihail; Krysiak, Yasar; Kolb, Ute; Tremel, Wolfgang
Abstract: Concrete is the most prevalent manufactured material that has shaped the built environment, but the high‐temperature production of cement, the main component of concrete, has a massive carbon footprint. It is shown that CO2 emissions during clinker production of cement can be circumvented by a metathesis reaction at room temperature in ball‐mills, where the cement clinker is replaced by non‐calcined limestone and alkali‐activated binders/geopolymers. An amorphous intermediate (aNaSiCC) containing a random mixture of the ionic constituents in "molecular" dispersion is formed by mechanochemical activation of CaCO3 and Na2 SiO3 . This allows molecular transport during crystallization and low activated reactions, as precipitation of solids from liquids (nucleation limited and kinetically controlled) and solid‐state transformations (diffusion‐limited and thermodynamically controlled) have equal weight. Several steps of the hydration reaction could be resolved. Activating the amorphous aNaSiCC precursor with NaOH leads to a CSH‐like phase with a C/S ratio of ≈1 containing some sodium. The carbonate components pass through a multistep crystallization from aNaSiCC via pirssonite and gaylussite to monohydrocalcite. The findings help unravel the interplay between thermodynamics and kinetics in complex reactions of alkali‐activated binders and for CaCO3 crystallization in industrial and geochemical settings, where dissolved silicate is always involved. Abstract : Ball milling of calcite and sodium metasilicate leads to "activated" amorphous sodium calcium silicate carbonate (aNaSiCC). Diffusion‐controlled crystallization of aNaSiCC in water/acetonitrile mixtures induced crystallization via pirssonite and gaylussite to monohydrocalcite. Alkali activation with NaOH leads to the CSH‐like phase, enabling the formation of a concrete binder without the need for high‐temperature calcination and emission of CO2 .